Pengayaan Materi Praktikum Akuntansi Instansi Pemerintahan bagi Tim MGMP Akuntansi SMK Provinsi Sumatera Barat - Vita Fitria Sari; Dewi Pebriyani; Mayar Afriyenti (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
The implementation of the 2013 revised 2017 curriculum in Vocational High Schools has introduced the field of government accounting in the SMK curriculum with the subject "accounting practicum for government institutions / agencies". The 2013 curriculum introduces the terms remedial and enrichment in the learning process. The challenge in the future of professionalism faced by teachers is how teachers can develop the existing potential for students who can quickly understand the material that has been given considering that the field of government accounting is a new field of accounting for SMK accounting teachers. This PKM aims to provide material enrichment for the subject of "practicum accounting for government institutions / agencies" consisting of PPKD financial report preparation and government financial report consolidation. The implementation method applied in this PKM is capacity building and workshops. At the end of the activity the participants were able to understand 73.65% of the important material for PPKD accounting and consolidation of regional government financial reports and were able to solve cases of PPKD financial report preparation and consolidation of regional government financial statements independently and correctly